RNA splicing in health and disease - Huining Huang; Yao Yu; Qian Zhou; Guangtong Deng; Yayun Li; Furong Zeng (Molecular Biomedicine, 2026)
Abstract RNA splicing expands the functional output of eukaryotic genomes by enabling individual precursor messenger RNA (pre-mRNA) to generate multiple mature transcripts with protein‑coding and regulatory properties. Its fidelity and plasticity depend on coordinated interactions among the spliceosome, trans-acting splicing factors, cis-regulatory elements, and chromatin- and RNA-associated regulatory mechanisms. However, how these components collectively generate cell- and tissue-specific splicing programs, and how their disruption drives disease, remain incompletely understood. In this review, we integrate the molecular regulation of RNA splicing with its physiological, pathological and therapeutic consequences. We describe how spliceosome assembly, splicing regulatory elements, splicing factors, epigenetic modifications, and post-transcriptional processes determine splice-site selection. We then examine how regulated isoform programs support development, tissue specialization, homeostasis, circadian timing, and stress adaptation, and how their failure contributes to cancer and diverse non-neoplastic diseases. In cancer, we highlight the bidirectional interplay between splicing dysregulation and the tumor microenvironment, through which metabolic reprogramming and immune suppression reinforce aberrant splicing. Finally, we assess strategies that modulate the spliceosome, splicing-factor activity, or disease-associated transcripts, and present a perspective on how multi-omics, artificial intelligence, targeted delivery, and combination with immunotherapy could collectively advance the discovery and precision of splicing-directed therapies. We suggest that safe clinical translation will require greater selectivity, reduced off-target toxicity, and preservation of essential physiological splicing.